The role of online and social media in combating sexual harassment in Egypt - Saleh, Mariam (AUC Knowledge Fountain, 2018)
Violence against women - particularly sexual harassment is a widespread problem faced by women around the world. In Egypt, research shows that a large number of women have been harassed at least once in their lifetime. The Egyptian Government, international organizations and non-governmental organizations have been working for several years on interventions and activities to combat sexual harassment. With the widespread use of online and social media in Egypt, this new media became a better and easily accessible form of conveying combating sexual harassment messages. This study, thus, aims to identify ways through which online and social media could be used through development communication campaigns to combat sexual harassment in Egypt. The study is based on a theoretical framework built on the Social Ecological Model, and seeks to identify how online and social media could be utilized along its five levels to combat harassment through social change, social mobilization, and advocacy. The study uses the single exploratory case study of HarassMap - an Egyptian NGO working on combating sexual harassment through online and social media. Theoretical propositions were developed for each of the five levels, and based on a content analysis of HarassMap's website and Facebook Page, the theoretical propositions were verified and modified. Findings of the study show that online and social media could be used through functional participatory communication campaigns, following a social change and social mobilization approach to: (1) encourage sexual harassment survivors to respond to harassment through changing beliefs, increasing self-efficacy, and changing behavior through social prompting; (2) encourage bystander intervention through changing beliefs, increasing bystander-efficacy, and changing behavior through social prompting; (3) change the society's attitudes and beliefs as related to assignment of responsibility and attribution of sexual harassment and increase the society's collective-efficacy to fight acceptability of harassment; (4) advocate for organizational change to have sexual harassment-free workplaces/educational institutions through targeting the organization and its surrounding environment; and (5) advocate for more stringent sexual harassment law/law enforcement.